RIYADAH TAREKAT SEBAGAI TERAPI KELUARGA MUSLIM - Aspiyah Kasdini (Syifa al-Qulub, 2020)
This research proves that riyadahthat practiced by sufis can be an alternative solution to solve various kinds of household problems, especially divorce. Riyadahis one form of therapy, which has a role in educating themselves and train the soul to control all forms of ego in order to form a good person's morality. This thesis aims to emphasize the results of Faisal Bahar Susanto (2006), Ermi Suryani (2014), Zakaria Husin Lubis (2013), Muhammad Tahir Khalily (2012), Ellen J. Amster, Ira Ratna Mahayanti (2013), Frank D. Fencham (2006), María del Rosario González Martín (2011), which proves that disciplinary or soul-setting exercises (riya>dah), contained- in the world of Sufism and the values contained therein (such as the value of monotheism and forgiveness)- has a role that governs various aspects of life. Based on previous relevant studies, no one has specifically addressed the theme and the case that we proposed, to fill the void, then herein lies the position of this research. This research is qualitative research by using observation, interviews, and documentation of the object of research as the main sources, and for secondary sources we use journals, dissertations, theses, and scientific books relating to themes and research cases. This research is a field research using phenomenology and psychology approach. The overall data obtained then presented using the method of critical analysis with the approach of science Sufism and Psychology.